2015
DOI: 10.1021/acs.iecr.5b03384
|View full text |Cite
|
Sign up to set email alerts
|

Poly(butylene succinate-co-adipate) Green Composites with Enhanced Rigidity: Influences of Dimension and Surface Modification of Kenaf Fiber Reinforcement

Abstract: Kenaf fibers (KFs) were utilized as reinforcements to prepare poly(butylene succinate-co-adipate) (PBSA) green composites. Untreated KFs of KF35 (large dimension) and KF120 (small dimension) imparted the nucleation effect for PBSA crystallization. KF120 exhibited superior nucleation efficiency compared with KF35. The tensile/flexural moduli of PBSA drastically increased after the addition of KF35 or KF120. Successful modifications of KF35 through NaOH(aq) and 3aminopropyltriethoxysilane (APS) were confirmed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Neat BioPBSA showed a tensile modulus (E) of 281 MPa, a tensile strength of 21.1 MPa, and an elongation at break of 313.6%. These are typical values for this polymer, similar to those reported by other authors [ 42 , 43 ]. These values are indicative of a material with high ductility but with some stiffness.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Neat BioPBSA showed a tensile modulus (E) of 281 MPa, a tensile strength of 21.1 MPa, and an elongation at break of 313.6%. These are typical values for this polymer, similar to those reported by other authors [ 42 , 43 ]. These values are indicative of a material with high ductility but with some stiffness.…”
Section: Resultssupporting
confidence: 92%
“…The melting points of the composites ranged between 86.1 °C and 88.2 °C. Chiu et al [ 42 ] obtained similar fusing temperatures in composites of PBSA with kenaf fibers, with T m varying between 88–89 °C. The addition of a plasticizing agent such as DBI and compatibilizing agents such as PBSA- g -IA and PBSA- g -MA did not alter the T m of the composites.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the use of LDHs as heat stabilizers and acid scavengers in halogenated polymers (such as PVC) is well known and is used on industrial scale [ 17 ], their use in biodegradable polymers to tune the durability and gas permeability properties has only just recently been reported. For example, recent studies have shown that addition of LDH to neat PBSA can enhance mechanical and gas barrier properties as well as prolong thermal and photo-durability [ 18 , 19 , 20 , 21 ]. Furthermore, previous studies have reported that LDH fillers have in general a catalytic effect on the biodegradation or hydrolytic degradation of different biodegradable polyesters such as poly(lactide acid) and polycaprolactone [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical, barrier and thermal properties of the neat PBSA are still not sufficient to widen its end-use applications. 31,32 To increase the performances of PBSA, composites have been prepared with polystyrene/titanium dioxide electrospun fibers, 31 graphene oxide, 32 organo-modified montmorillonite, 33,34 halloysite nanotube, 35 kenaf fibers, 36 hydrolyzed collagen, 37 rutile TiO 2 , 38 and hexadecylamine-modified layered zinc phenylphosphonate. 39 PBSA composites with sorbitol and oleic acid modified LDHs have been reported by Chen et al: the authors discussed about the biodegradation, which was hindered by LDH.…”
Section: Introductionmentioning
confidence: 99%